Application of the Hormone rEIGH (Recombinant Growth Hormone) in Gel Feed in Spurring the Growth Rate of Male Gift Tilapia (Oreochromis niloticus) Sex Reversal Results - Syahrir Syahrir (Central Research Institute For Agriculture, 2021)
This study aims to analyze the efficiency of gel feed as a growth hormone carrier agent on survival rate, relative growth rate, feed conversion ratio (FCR), feed consumption rate, from the average condition factor of male gift tilapia resulting from sex reversal treated with rEIGH hormone. using gel feed at different doses. This research was conducted in April-May 2017 at the Hatchery of the Faculty of Marine Science and Fisheries, Hasanuddin University, Makassar. The test animals used were tilapia seeds aged 57 days which were stocked at a density of 22 fish/aquarium with a size of 37x40x34 cm. The test feed given was gel feed containing different rEIGH hormone doses. Parameters measured were survival, relative growth, food conversion ratio (FCR), feed consumption rate, and condition factors. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Gel feed containing rEIGH at doses of 0.015, 0.030 and 0.045 g/kg feed, as well as control (without rEIGH) were given three times a day for 1 month. The results of the analysis of variance (ANOVA) showed that the test feeds containing different rEIGH hormone doses had no significant effect (p>0.05) on survival, relative growth, FCR, feed consumption level, and the average condition factor of the tested fish.